PERAN MEDIASI UKURAN PERUSAHAAN PADA PENGARUH ASIMETRI INFORMASI DAN ANALYST COVERAGE TERHADAP KONSERVATISME AKUNTANSI PADA PERUSAHAAN SEMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Maryanto Maryanto (Institut Agama Islam Negeri Kerinci, 2021)
ABSTRACT Purpose: This study aims to determine whether there is an effect of Information Asymmetry on Accounting Conservatism, Information Asymmetry on Firm Size, Analyst Coverage on Accounting Conservatism, Analyst Coverage on Firm Size, Firm Size on Accounting Conservatism, Information Asymmetry and Analyst Coverage on Accounting Conservatism through Size Company as an intervention. Design/methodology/approach: The data processing of this research uses path analysis to explain the direct or indirect effect of a set of independent variables on the dependent variable. Findings: The results show that there is no influence between Information Asymmetry on Accounting Conservatism, there is no influence between Information Asymmetry on Company Size, there is no influence between Analyst Coverage on Accounting Conservatism, There is an influence between Analyst Coverage on Company Size, there is no influence between Analyst Coverage and Firm Size. Firm Size on Accounting Conservatism, Firm Size does not act as an intervening between Information Asymmetry and Accounting Conservatism, Company Size does not act as an intervening between Analyst Coverage and Accounting Conservatism.